Bi5O7Br-nanotube@Au-nanoparticle core-shell assembly for high signal-to-noise ratio SERS detection of adenine. (March 2023) - Feng, Ran; Meng, Jiazhi; Yuan, Hualei; Zhang, Xu; Gao, Chunlang; Ban, Chaogang; Guo, Yizhong; Wang, Kaiwen
Abstract: Cancers, Down's syndrome, Alzheimer's and other diseases of gene mutation always occur with anomalous changes of DNA nucleic acid base. Therefore, the development of highly sensitive and reproducible nucleic acid sensors that based upon surface enhanced Raman scattering (SERS) is of immense interest for clinical medical analysis and diagnosis. Herein, a rationally designed core-shell assembly of Au nanoparticle wrapped with Au doped Bi5 O7 Br nanotube with eliminated fluorescent background and notable chemical enhancement effect was exploited and served as a SERS sensor for detection of adenine. Especially, we found the fluorescent background was remarkably suppressed in Raman spectra by introducing Au element into Bi5 O7 Br. The sensor exhibited a maximum SERS enhancement factor of up to 5.45 × 10 7 and a detection limit as low as 10 −11 M after constructing Au nanoparticle/Au atom doped Bi5 O7 Br heterojunction. More importantly, good reproducibility and long term stability under work condition were achieved. To gain in-depth understanding into chemical mechanism (CM) of the Raman signal enhancement, density functional calculations (DFTs) were combined with atom-specific model derived via aberration corrected transmission electron microscope (AC-TEM) to demonstrate the enhanced charge transfer (CT) and substrate-adsorbate adsorption. The doping and coupling strategy holds the potential to fabricate high signal-to-noise ratio SERS sensors for other molecule detection. Graphical Abstract: Bi5 O7 Br-nanotube@Au-nanoparticle core-shell assembly was exploited as SERS substrate. The limit of detection for Adenine was as low as 1.0 × 10 −11 M, which is one order of magnitude lower than that of colloidal Au NPs (1.0 × 10 −10 M). The analytes can be extended to G, C, T. ga1 Highlights: Bismuth oxybromide-based material (Bi5 O7 Br-nanotube@Au-nanoparticle) was exploited as SERS substrate. The limit of detection for adenine was as low as 1.0 × 10 −11 M, which is one order of magnitude lower than that of colloidal Au NPs (1.0 × 10 −10 M). The analyte can be extended to other nucleic acid bases such as G, C, T. The up-shifted band center and high electron state densities near Fermi level may account for the enhanced charge transfer.